Determinants of Governance and Financial Reporting Performance: Budget Participation, Supervision, and Leadership Style - Husmaruddin Husmaruddin; Salju Salju; Goso Goso; Junaidi Junaidi (Studi Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study aims to examine the effects of budget participation, budget supervision, and leadership style on governance and local government financial reporting performance in South Sulawesi, Indonesia. Methodology: This quantitative study was conducted in 24 regencies and cities in South Sulawesi, Indonesia. Data were collected through a questionnaire survey involving 382 respondents consisting of budget authorities from Regional Government Work Units (SKPD) and members of Regional People's Representative Council (DPRD). The data were analyzed using Structural Equation Modeling (SEM) with AMOS 22 and SPSS 22 to test the research hypotheses. Results: The findings indicate that budget supervision significantly improves governance, and leadership style significantly enhances financial reporting performance. Governance also has a positive effect on financial reporting performance and mediates the predictor effect of budget participation, budget supervision, and leadership style on local government financial reporting performance. However, budget participation does not have a significant direct influence on governance or financial reporting performance. Conclusions: Effective supervision and adaptive leadership are important determinants of strengthening governance and improving the quality of financial reporting in local governments. Limitations: This study is limited to local governments in South Sulawesi and relies on self-reported questionnaire data, which may limit its generalizability. Contributions: This study contributes to the public sector accounting and governance literature by providing empirical evidence on the role of participatory budgeting, supervision, and leadership in improving governance quality and financial reporting performance, offering practical insights for policymakers and public sector institutions.